1984
DOI: 10.3102/01623737006001073
|View full text |Cite
|
Sign up to set email alerts
|

High School Size, Participation in Activities, and Young Adult Social Participation: Some Enduring Effects of Schooling

Abstract: at are the effects of schools on students? Do differences in organizational structure affect patterns of behavior within schools, thus contributing to these effects? To what extent does education affect not only short-term academic achievement, but long-term adult behavior? Such questions are at the heart of research in sociology of education. Usually, however, the problem has been posed as the relationship of education to work and socioeconomic status. The parallel question of the effect of education on leisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 19 publications
1
25
0
2
Order By: Relevance
“…Accordingly, the positive outcomes and behavior changes associated with extracurricular activity participation may reflect processes that were not considered. School- related factors (Barker & Gump, 1964;Chase, Jacobs, & Meredith, 1987;Eder, 1985Eder, , 1995Jacobs & Chase, 1989;Karweit, 1983;Kinney, 1993;Lindsay, 1984), family influences (Csikszentmihalyi, Rathunde, & Whalen, 1993;Fletcher, Elder, & Mekos, 1997;Jones & Offord, 1986, 1989Mahoney, 1998), and individual differences in motivations or aspirations (Clausen, 1993;Hymel et al, 1996;Pickles & Rutter, 1991;Vallerand, Fortier, & Guay, 1997) may each influence whether an individual becomes involved in school activities. These factors should be pursued in future research (Brown, 1988;Hultsman, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the positive outcomes and behavior changes associated with extracurricular activity participation may reflect processes that were not considered. School- related factors (Barker & Gump, 1964;Chase, Jacobs, & Meredith, 1987;Eder, 1985Eder, , 1995Jacobs & Chase, 1989;Karweit, 1983;Kinney, 1993;Lindsay, 1984), family influences (Csikszentmihalyi, Rathunde, & Whalen, 1993;Fletcher, Elder, & Mekos, 1997;Jones & Offord, 1986, 1989Mahoney, 1998), and individual differences in motivations or aspirations (Clausen, 1993;Hymel et al, 1996;Pickles & Rutter, 1991;Vallerand, Fortier, & Guay, 1997) may each influence whether an individual becomes involved in school activities. These factors should be pursued in future research (Brown, 1988;Hultsman, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have provided evidence that if students participate in activities when they are young, they are more likely to participate in organizations and in the political process when they are older (Beck and Jennings, 1991;Almond and Verba, 1963;Verba et al, 1995;Rosenstone and Hansen, 1993). Lindsay (1984) finds that participation in extracurricular activities in high school is even more important than educational attainment as a predictor of participation in voluntary activities as an adult. Put another way, if young people do not become involved in their community in their youth, they are more likely to remain detached when they are adults.…”
Section: Political Engagementmentioning
confidence: 98%
“…Students in small schools evidently perceive ample extracurricular opportunity (National Center for Education Statistics, 1995) and participate at a higher frequency than do students at large schools. In a national sample of seniors, Lindsay (1982Lindsay ( , 1984 reported that participation correlated -.22 with school size. 39 Student attitudes.…”
Section: Student Characteristicsmentioning
confidence: 99%
“…Larger school enrollment is directly related to the comprehensiveness of the curriculum and therefore expands a student's course-taking possibilities (Monk & Haller, 1993). On the other hand, smaller school enrollment expands a student's possibilities for extracurricular achievements, because fewer people are competing for limited positions of honor (Lindsay, 1982(Lindsay, , 1984. Holland and Andre (1987, p. 437) argued that, as a consequence, "Low-ability and lower SES students are more involved in school life in smaller schools."…”
Section: Adjusting For Grading Variationsmentioning
confidence: 99%